To protect or adversely affect? The dichotomous role of the NLRP1 inflammasome in human disease. (December 2020) - Tupik, Juselyn D.; Nagai-Singer, Margaret A.; Allen, Irving C.
Abstract: NLRP1 is an inflammasome forming pattern recognition receptor (PRR). When activated by pathogen- and damage- associated molecular patterns (PAMPS/DAMPS), NLRP1 inflammasome formation leads to inflammation through the production of proinflammatory cytokines IL-18 and IL-1β. As with other inflammasome forming NLR family members, NLRP1 also regulates cell death processes, termed pyroptosis. The domain structure of NLRP1 differs between mice and humans, making it possible for the function of the inflammasome to differ between species and adds complexity to the study of this NLR family member. In humans, mutations in both coding and non-coding regions of the NLRP1 gene are linked to a variety of diseases. Likewise, interruption of NLRP1 inhibitors or changes in the prevalence of NLRP1 activators can also impact disease pathobiology. Adding to its complexity, the NLRP1 inflammasome plays a dichotomous role in human diseases, functioning to either attenuate or augment miscellaneous biological processes in a tissue specific manner. For example, NLRP1 plays a protective role in the gastrointestinal tract by modulating the microbiome composition; however, it augments neurological disorders, cardio-pulmonary diseases, and cancer through promoting inflammation. Thus, it is critical that the role of NLRP1 in each of these disease processes be robustly defined. In this review, we summarize the current research landscape to provide a better understanding of the mechanisms associated with NLRP1 function and dysfunction in human disease pathobiology. We propose that a better understanding of these mechanisms will ultimately result in improved insight into immune system dysfunction and therapeutic strategies targeting inflammasome function in multiple human diseases.